Science, freedom, democracy - Hartl, Péter; Tuboly, Ádám Tamás 1988- (Routledge / Taylor, 2021)
Science, freedom, democracy : introduction / Péter Hartl and Adam Tamas Tuboly -- Michael Polanyi's post-critical vision of science and society / Phil Mullins -- The ethos of science and central planning : Merton and Michael Polanyi on the autonomy of science / Péter Hartl -- Scientific freedom and social responsibility / Heather Douglas -- Bacon's promise / Janet Kourany -- Which science, which freedom, and which democracy? / Hans Radder -- Participatory democracy and multi-strategic research / Hugh Lacey -- Are transparency and representativeness of values hampering scientific pluralism? / Dustin Olson -- Are transparency and representativeness of values hampering scientific pluralism? / Jeroen Van Bouwel -- Max Weber's value-judgment and the problem of science policy-making / Lidia Godek
Includes bibliographical references and index
Keywords: Akademische Freiheit; Wissenschaftsfreiheit; Forschungsfreiheit; Demokratie; Science / Social aspects; Science / Political aspects; Research / Social aspects; Research / Political aspects; Academic freedom; Democracy and science; Pluralism; Aufsatzsammlung